NEW WAYS OF GROWING YOUNG PIGS IN INNOVATIVE TYPE STALLS - Ivanov, V. O.; Onyshchenko, A. O.; Zasukha, L. V.; Hryhorenko, V. L. (Scientific Progress & Innovations, 2020)
The introduction of intensive technologies of pork production is one of the priority directions of agro-industrial complex development. The analysis of publications enabled us to conclude that over the last dec-ade a large number of equipment for keeping pigs using two-phase technology has been developed. The aim of the study was to improve the methods of growing young pigs in innovative type stalls. A new method of growing young pigs has been developed, and a device for its implementation has been designed, which is a four-section block-stall, which enables to feed sows and weaned piglets with concentrated, roughage and green feed; to unite 21-day-old piglets in four-, three-, two- and single-pen groups depending on their prolif-icacy and heavy farrowing, to grow them stress-free after weaning until 65–90 days of age and transfer to fattening in group stalls designed for keeping four-, three-, two- and one-pen groups. The results of the re-search show that the proposed methods of combining piglets’ pens had some effect on piglets’ growth during the suckling period. Piglets of the fourth group had a slight tendency to increase live weight in comparison with analogues of other groups. A much more significant difference between the experimental groups can be traced after weaning piglets. Thus, piglets of group IV surpassed the analogues from group I by 11.41 %, at the age of 65 days and at 90-day age – by 11.09 %. Piglets of group III also surpassed the analogues from group I by 7.17 % at the age of 65 days and at 90-day age – by 8.04 %. It was found that according to the new method of growing piglets in one (group IV), two (group III), three (group II) and four (group I) pens, the following results were obtained: the age of reaching live weight of 100 kg was, respectively, 170.02±2.64 (IV); 172.77±1.83 (III); 174.31±1.41 (II); 178.02±1.43 (I) days, the average daily gain in weight of pigs for fattening – 781.34±7.05 (IV); 768.24±6.12 (III); 762.31±7.37 (II) and 745.23±6.26 (I) g; feed consumption per unit of weight gain – 3.02±0.02 (IV); 3.11±0.02 (III); 3.15±0.03 (II) and 3.28±0.02 (I) kg.